Evaluation and Management of Unresectable Hepatocellular Carcinoma: Multidisciplinary Indian Consensus Statements from a Delphi Panel - Ramaswamy, Anant; Shukla, Akash; Engineer, Reena; Sundaram, Sridhar; Srinivas, Sujay; Kulkarni, Suyash; Patkar, Shraddha; Baijal, Sanjay; Kale, Aditya; Kapoor, Akhil; Mukund, Amar; Choudhari, Amit; Rauthan, Amit; Mathew, Ashwathy Susan; Panchal, Rushi; Bhattacharya, Kausik; Patil, Prachi; Shetty, Nitin; Gala, Kunal; Kumar, Lijesh; Thiruchunapalli, Deepashree; Kalra, Naveen; Sahoo, Tarini Prasad; Krishna, M Vamshi; Lavingia, Viraj; Mohanka, Ravi; Talwar, Vineet; Ostwal, Vikas; Bhargava, Prabhat; Poddar, Jyoti; Singal, Amit; Goel, Mahesh (South Asian Journal of Cancer, 2024)
Background India, like many parts of Asia, likely faces a high burden of hepatocellular carcinoma (HCC), though large-scale data on etiology, presentation, and outcomes are lacking. There appears to be a predominance of unresectable, advanced-stage HCC at presentation in India with variable level of expertise in India to manage these scenarios. This publication summarizes the latest evidence with cognizance of the unique challenges faced in India by treating clinicians.Methods A multidisciplinary panel of medical oncologists, gastroenterologists, hepatologists, interventional radiologists, and hepatobiliary surgical oncologists held a meeting in June 2022 and reviewed the evidence available for management of HCC. The meeting concentrated on the recognition and management of HCC not amenable to surgical approaches in the Indian context. A literature review of these aspects of management was conducted and consensus statements with level of evidence and grades of recommendation were prepared by individual specialists in each field. Statements were evaluated by the modified Delphi method.Key Content and Findings The panel comprising 22 experts formulated 40 consensus statements with regard to defining unresectable HCC, optimization of underlying conditions prior to management, rationale use of various liver-directed therapies (LDTs) in unresectable HCC, and systemic therapeutic options in this group of patients.Conclusion Our consensus statements offer practical, yet evidence-based management guidelines for treating unresectable HCC in the Indian context. There is an emphasis on the crucial need for combining available approaches for LDT, even if less well studied though possibly effective, with standard systemic therapy.
Keywords: HCC; hepatocellular carcinoma; Indian consensus; MDT; multidisciplinary tumor board